Técnicas persuasivas da retórica aristotélica: um estudo a partir dos discursos produzidos nas regências do Estágio Supervisionado I em Ciências Biológicas de uma Universidade Pública no Estado do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This dissertation aims to study the speeches produced in the regencies of the Supervised Internship in Biological Sciences from the perspective of Aristotelian rhetoric. The study was developed with the objective of identifying persuasive techniques of Aristotelian rhetoric in the speeches produced in the regencies of the Supervised Internship I in Biological Sciences of a Public University in the State of Paraná. It was outlined through the following problem-question: to what extent are persuasive techniques of Aristotelian rhetoric present in the speeches produced in the regencies of the Supervised Internship in Biological Sciences? As a methodological design, field research was adopted, with a qualitative approach, descriptive and interpretative nature (Lüdke; André, 2022). The theoretical foundation used - based on the mapping done on the State of Knowledge (Morosini; Santos; Bittencourt, 2021) of scientific production related to Aristotelian rhetoric in Brazil; and on the examination of the Aristotelian conception of rhetoric based on the works of Aristotle (Rhetoric, 2012; Nicomachean Ethics, 1991; and Topics, 2021) - allowed the identification of four mediation instruments: 1) exposition; 2) demonstration; 3) clarity and 4) example. Through them, the theoretical device of the research was composed. Empirical data were obtained - in the field - through participant observation (Lüdke; André, 2022) in nine regencies, of which seven were gathered and transcribed to compose the unit of analysis of the research. They were accessed and interpreted through the correlation of two devices (theoretical and analytical) of the discourse analysis technique supported by Orlandi (2015). The correlation performed resulted in capturing the immediate context of the discursive interaction between the subjects involved in the speeches and showed that the persuasive techniques analyzed constitute discursive properties incorporated into teaching practice, which operate interconnectedly and act as a kind of “force that acts at a distance” in negotiating distances, regardless of whether they are known or not. The results point to the need to understand persuasion as a property incorporated into teaching practice (performance) and inherent in the act of teaching (sciences). With this research, the practice of methodical persuasion is postulated as a “good ally” for circumstances that require “practical judgment” (phronesis) and as a resource through which the sense of methodical persuasion can be tensed, expanded, and worked from the Supervised Internship as a subsidy for teaching practice in the act of teaching sciences.
Keywords: persuasão metódica; prática docente; Estágio Supervisionado; Ensino de Ciências; methodical persuasion; teaching practice; Supervised Internship; Science Teaching; CNPQ::CIENCIAS HUMANAS::EDUCACAO